Studi Korelasi Pola Asuh, Religiusitas dengan Impulse Buying pada Mahasiswa Universitas Islam Bandung - Anna Rozana; Eni Nuraeni Nugrahawati; Dinda Dwarawati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
This research aims to study about correlation between parenting, religiusity and impulse buying among Bandung Islamic University students who join pesantren for bachelor candidate. This research used correlation research design involving 420 students of Bandung Islamic University who join pesantren for bachelor candidates of 2016. Subjects are between 18-21 years old from some faculties which are engineering, science, dakwah, communication, teacher training, ekonomics, law, syariah and psychology. Result shows that 328 students are in impulse buying category. However, parenting and religiusity are not significant variables effecting impulse buying phenomena. Further research suggested to deepen parenting variable since related to impulse buying behaviour.